Caspian Sea Level Change and its Environmental Impacts on the Geopolitics of the Region - Afshin Motaghi; Mostafa Mohammadjani (Emerging Issues in Environment, Geography and Earth Science Vol. 7, 2024)
Caspian Sea level has experienced considerable fluctuations over the past years. Therefore, due to the unfavorable conditions of changes in Caspian Sea and also the impacts created on its surrounding ecosystems, it has increased the importance of this issue during recent decades. Accordingly, the present study examined and analyzed the trend of Caspian Sea water level changes in a long-term period (1990-2023). Also, in the current study, the effects caused by the fluctuations of Caspian Sea level were examined from various environmental, social and economic aspects. For this purpose, a set of images of Landsat 5 for 1990 and Landsat 8 for 2023 was analyzed in the Google Earth Engine (GEE) web system. The results showed that the variations of Caspian Sea level (North, Middle and South) during the period 1990 to 2023 indicate a decline of 2.34 m in the sea level. Also, it was found that the water level of Caspian Sea in 1990 was -26.18 m, and these changes reached -28.52 m in 2023. Thus, the water of Caspian Sea has experienced fluctuations during recent decades, and these changes have led to threats in infrastructure, economic and social uses, disturbance in the activity of ports and seafaring, fishing, and drying up of water reserves related to Caspian Sea (wetlands - bays), the increase of the coastal area, human occupation of the sea and adverse effects on the coastal aquifers. In this regard, the management of these issues requires a cross-sectoral and comprehensive approach within the framework of integrated coastal management.